Accountantalizing / Azlina Rahim ... [et al.] - Rahim, Azlina; Abu, Nor ‘Asyiqin; Mamat, Siti Nurulhuda; Saidin, Amilia (Universiti Teknologi MARA, Kedah, 2019)
Smartphone technology has evolved enough to turn the boring lecture into an exciting learning system by means of educational mobile apps. By 2019, 74% of e-learners use smartphones for e-learning (www.ambientinsight.com). AccounTantalizing is about making genuine improvement, especially to foster the learning process through digital technology. AccounTantalizing helps to maintain the learning process even outside the classrooms. Excessive information during class along with textbooks and notes that only contain words and figures causes accounting subject as heavy and dull thus subsequently affect students’ performances since they may be lazy to read. By combining core accounting subjects such as financial accounting, management accounting, taxation and auditing in AccounTantalizing, it removes the hassle of retrieving information from many sources. It provides a platform for students and learners to get information easily. Moreover, as a one-stop center, AccounTantalizing offers various contents such as videos, slides, Q&A, illustrations, web links, and articles related to their subjects. AccounTantalizing is only a finger away from phone that makes students’ life better and easier. Via internet access, students can use AccounTantalizing wherever they are and can be accessed anytime without password. AccounTantalizing is expected to be well accepted since accounting program is offered in most local universities. AccounTantalizing also support green environment where it is paperless and can save environment. Lastly, there is no denial that mobile apps are the future and add value to tomorrow’s economic and social culture.